The Effect of Quality Management on Employee Work Effectiveness at Mulyasari Hospital Jakarta - Mahati, Fathya; Irawan, Pristanto Ria; Taryanto, Taryanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Hospitals as health care institutions have a vital role in improving public health status. In carrying out its functions, the hospital is required to provide quality and effective services. One of the key factors in realizing this is through the implementation of good quality management. Quality management is a systematic approach to improving the quality of services and work processes in an organization. In the health sector, the implementation of quality management aims to improve patient safety, customer satisfaction, and operational efficiency. The purpose of this study was to determine the effect of quality management on employee work effectiveness at Mulyasari Hospital Jakarta. This study uses a quantitative descriptive method with data collection techniques through distributing questionnaires, and library data. In this study using a saturated sampling method totaling 40 employees at Mulyasari Hospital Jakarta with simple linear regression data analysis techniques. The results of this study indicate that there is a partial quality management effect on employee work effectiveness at Mulyasari Hospital Jakarta. The results of this study are expected to contribute to further research.